2014
DOI: 10.3892/br.2014.402
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D receptor polymorphisms and haplotypes with pulmonary tuberculosis

Abstract: Abstract. The vitamin D receptor (VDR) is an important factor in activating immune response in different infectious diseases. The aim of the present study was to investigate the association between the VDR gene polymorphisms and pulmonary tuberculosis (PTB). The case control study was performed on 120 PTB patients and 131 healthy controls. Genetic analysis was performed by polymerase chain reaction and the restriction fragment length polymorphism method. The VDR Fok1 Ff genotype was associated with TB and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…The presence of Single Nucleotide Polymorphisms (SNP) was reported on this gene. The Restriction Fragment Length Polymorphism (RFLP) for FokI, BsmI, ApaI and TaqI restriction enzymes is used nowadays in genetic susceptibility studies of infectious diseases [11]. TaqI polymorphism (rs731236; T>C) results from the change of thymine to cytosine (ATT to ATC).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Single Nucleotide Polymorphisms (SNP) was reported on this gene. The Restriction Fragment Length Polymorphism (RFLP) for FokI, BsmI, ApaI and TaqI restriction enzymes is used nowadays in genetic susceptibility studies of infectious diseases [11]. TaqI polymorphism (rs731236; T>C) results from the change of thymine to cytosine (ATT to ATC).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from population studies suggests that vitamin D deficiency is highly prevalent among the general population in China, which may be related to genetic variation in VDR [16]. Previous studies have shown that VDR genetic variants (such as rs1544410, rs7975232 and rs731236) can participate in the development of various tumors (such as prostate cancer and hepatocellular carcinoma) by affecting the biological effects of vitamin D [17,18]. Shortly thereafter, vitamin D deficiency was found to be associated to immune-related diseases (systemic lupus erythematosus) and infectious diseases (tuberculosis) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have revealed that VDR gene polymorphism is significantly associated with an increased risk of PTB in Venezuela, Iran, Turkey, and Han Taiwanese populations . Molecular epidemiological studies have also revealed that VDR polymorphism is significantly associated with an increased risk of PTB in tribal population of Chhattisgarh and southeastern region of India .…”
Section: Discussionmentioning
confidence: 99%